Culture and commerce : the value of entrepreneurship in creative industries - Khaire, Mukti, 1973- (Stanford Business Books, an imprint of Stanford University Press, 2017)
Highlighting the roles and functions of three essential players--creators, producers, and intermediaries--this book leads readers to better understand the nature of creative industries and the impact that they have on business and culture.